Forensic heritage. A research agenda on the material and expressive processes of the public memorialisation of violence in post-authoritarian contexts - Blanes, R. L.; Oliveira, P. A.; Prista, M.; Barros, M. de.; Temudo, A.; Ferreira, F. M.; Simões, S.; Ayán, X.; Barros, V.; Silva, M. C. da.; Mendes, F. A. (International Journal of Heritage Studies, 2025)
In this article, we propose a research agenda towards the critical assessment of processes of memorialisation and heritagization of histories of violence in post-violence and post-authoritarian contexts. Working from the perspective of postcolonial Bissau-Guinean, and based on an interdisciplinary collective brainstorm experiment held between sociologists, anthropologists, archaeologists, museum specialists and historians in Bissau-Guinean, some of whom with extensive knowledge of the country, the authors suggest the introduction of a ‘forensic methodology’ that enables the unveiling of the multilayered processes of heritage formation, and the exploration of the epistemological consequences of such processes.